DATA ANALYSIS AND PLAYER PERFORMANCE IN GAMES USING DATA API - de Oliveira, João Vitor Lemes; Graciano, Fernando Cesar (Revista Interface Tecnológica, 2022)
League of Legends (LOL) is a MOBA by Riot, with many fans around the world. Each player chooses a character, with specific abilities and roles, both to defend their base and to attack the opponent. The competitive scenario of LOL has been growing a lot around the world, thus existing in total of 12 Regions with 12 professional player leagues, each region has its main league and, in other cases, even lower divisions, as in Brazil. Application Programming Interface (API) It is a software layer that provides structured request and response. Allows software to communicate with other software in a simplified and secure way. An API is created so that other software developers can develop similar products on your service. In the world, there are several companies that make their codes available to another software company, so, for this reason, there are great similarities in applications, games, among other things. Keywords: Keywords. Keywords. Keywords. Keywords. Keywords.